Analisis Kemampuan Menerka Makna Kanji Rikusho Pada Mahasiswa Tingkat II Jurusan Bahasa Jepang Fakutas Bahasa dan Seni Universitas Negeri Jakarta - Hapsari, Eky Kusuma (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2016)
Japanese learners are required to have multiple intelligences in order to master kanjiparticularly Rikusho. Conducted in Japanese Department of Language and Art Faculty ofState University of Jakarta (UNJ) in 2015 with 43 respondents, the aims of this research isto know students’ level of competence in conjecturing kanji particularly in: 1) The use ofkai’i moji to represent countries, 2) The standardized form and the meaning of kanji basedon its origins and its’ classification based on rikusho. The results shows that therespondents’ level of competence is below average in conjecturing Kai’i Moji, mostly onaverage level in conjecturing standardized kanji with its meaning and in classifying kanjibased on types of rikusho.